Experimental Exclusion of Guanaco Grazing Increases Cover, Diversity, Land Function and Plant Recruitment in Patagonia - Cepeda, Carla Tamara; Oliva, Gabriel Esteban; Ferrante, Daniela (Tech Science Press, 2024)
Semiarid Patagonia represents 25% of the rangeland area in Argentina, and sheep overgrazing has degraded about a third of it in the past. In this century, depleted domestic stocks have mostly stabilized, but Guanaco populations have grown. These native camelids share habitat and diets with sheep, but their effect on vegetation is poorly understood and has long been debated. We set up an exclusion experiment in Monte León and Cañadón Vaca, a semiarid shrubland grassland in southern Patagonia, currently grazed only by guanacos. Vegetation baselines were studied in 2016 in twelve plots, and half of them were protected from guanaco grazing. Thirty-six plots were cleared to study revegetation. Vegetation was reassessed in 2021, and changes were evaluated using a paired t-test. Within protected plots, vegetation cover increased, bare soil diminished, and vegetated patches grew in size, but the density of the patch-interpatch arrangement did not change. Biodiversity, measured by richness and the Shannon-Wiener (SW) index, grew significantly. Nutrient recycling increased, as did the Stability and Infiltration Land Function indexes, although these last differences were not significant. Vegetation cover under guanaco grazing also increased, mainly due to the growth of dwarf shrubs, a typical tendency in sheep grazing-induced transitions in the region. Vegetated patches under grazing fragmented, resulting in smaller patches and denser patch structures, while diversity and land function indexes remained unchanged. Young plants established in cleared plots without guanacos showed higher cover density and individual size. These effects are similar to those observed in numerous experimental sheep exclosures. Guanaco grazing may thus prevent restoration and contribute to the generalized land degradation processes that overgrazing has been causing in Patagonia for over a century.